BEYOND CRITICAL THINKING IN ACADEMIC WRITING: A DISCOURSE PERSPECTIVE: DISCOURSE PERSPECTIVE Misdi, Nurani Hartini, Dian Farijanti, Department of English Education, University of Swadaya Gunung Jati Cirebon, Indonesia misdirina@gmail.com*, nuranihartini@gmail.com, dian_farijanti@yahoo.co.id - Misdi Misdi (Universitas Putera Batam, 2014)
The phenomenon of critical thinking, as one aspect of learning experiences, is challenging. Yet, it reflects students’ ideas and understanding of particular matters, especially in academic writing among the English education institutions. Thus, this study was aimed to investigate how undergraduate students fashioned their understanding of being self-driven in writing research proposal relating to reading skills. The research questions drop into two big areas: 1) How is critical thinking reflected in research proposal writing, 2) What are evidences of being critical in addressing research proposal? Having three sessions of in-depth interview, fifty seven students of English department of a private university in West Java, Indonesia were involved in the reflection of their writing and reading experiences during the study. The data were collected through interview and document observation. The findings suggest that first, the critical writing is reflected by such citation and elaborative sentences as the distinctive writing features of academic writing. Second, the extended description and elaboration are made due to reading constraint. Books are mainly the sources, whereas research journal articles are still less appreciated. Thus, reading is defines as the evidence of being critical. The results of the study play significant contribution in building critical thinking, critical reading, and critical writing as self-awareness manifesto among the students of English education.